Land tenure, industrialization, and social stability : experience and prospects in Asia - Froehlich, Walter (Milwaukee : Marquette University Press, 1961)
An inquiry into one of the most fundamental issues confronting the economies of Asian nations: namely the problem of land tenure and its relationship to economic, political, and cultural change.
"Collection of essays submitted to a conference jointly sponsored by the Institute for Asian Studies, the Graduate School, and the Department of Economics of Marquette University ... held in September 1959."
Includes bibliographical footnotes.
oif 28/01/2019
Loans
Keywords: Land tenure; Economic policy; Asia